Lung enteric-type adenocarcinoma with gastric metastasis: a rare case report and literature review - Li, Xiaoning; Ma, Kewei; Ma, Xiaobo; Zhao, Xiangye; Fan, Mengge; Xu, Yinghui (Frontiers in Immunology, 2024)
Lung enteric-type adenocarcinoma (ETAC) is a rare subtype of non-small cell lung cancer (NSCLC), comprising approximately 0.6% of all primary lung adenocarcinomas. It is characterized by a tendency for early metastasis and a prognosis comparable to that of common lung adenocarcinoma. This case report described a patient with lung-ETAC who developed gastric metastasis. The patient underwent treatment with chemotherapy and a PD-1 inhibitor, resulting in disease remission with a progression-free survival (PFS) of 8 months. The follow-up time was 13 months. This case report was aimed to enhance understanding of the biological behavior of this rare tumor and provide insights into potential future treatment strategies.